Combining face‐to‐face laboratory sessions and a computer simulation effectively teaches gene editing and DNA sequencing to undergraduate genetics students - Vedova, Chris Della; Denyer, Gareth; Costabile, Maurizio (Biochemistry and molecular biology education, 2025)
Innovative approaches to teaching genetics are essential for improving student engagement and comprehension in this challenging field. Laboratory‐based instruction enhances engagement with the subject while fostering the development of practical competencies and deepening comprehension of theoretical concepts. However, constraints on time and financial resources limit the feasibility of conducting extended laboratory sessions that incorporate cutting‐edge genetic techniques. This study evaluated a hybrid teaching method that combined face‐to‐face (F‐2‐F) laboratory sessions with an online simulation to instruct undergraduates on gene editing and DNA sequencing. A Unity‐based simulation was developed to complement traditional F‐2‐F laboratory sessions, allowing students to practice DNA sequencing techniques in a low‐stakes environment. The simulation was integrated into a course‐based undergraduate research experience (CURE) focused on CRISPR/Cas9 gene editing in yeast. Student performance, engagement, and perceptions were assessed through laboratory assignments, access logs, and surveys. Students who engaged with the simulation prior to F‐2‐F sessions and those who engaged with the simulation over multiple days performed significantly better in assessments. Survey results indicated that most students found the simulation realistic and relevant and reported enhanced learning of DNA sequencing principles. Student confidence in DNA sequencing knowledge increased significantly after using the simulation. Student feedback highlighted benefits such as improved procedural understanding, stress reduction, and increased preparedness for F‐2‐F sessions. This approach addresses logistical challenges of traditional laboratory education while providing students with authentic, repeatable experiences in complex techniques. Our findings demonstrate the potential of integrating simulations with F‐2‐F instruction to enhance undergraduate education in genetics and molecular biology.